Sociological Analysis of Islamic Law on The Implementation of the Jo Kawin Bocah Program in Reducing Early Marriage Rates (Case Study on the PKK Team of Temanggung Regency) - Rahmadani, Luqiya Suci; Ibrahim, Malik; Muhammad, Hanifah Salma (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
The